Ab initio prediction of thermoelectric performance of monolayer transition-metal nitride halides MNBr (M = Zr, Hf). (February 2022) - Liu, Xinyu; Yuan, Shaoheng; Xu, Bin; An, Xiaoning; Zhao, Jiahao; Li, Jifang; Yi, Lin
Abstract: Accurate descriptions of the structure, electronic properties and thermoelectric (TE) properties of transition-metal nitride halides MNBr (M = Zr, Hf) monolayers are calculated using the full-potential linearized augmented plane-wave (FP-LAPW) method within both generalized gradient approximation (GGA) and Tran–Blaha modified Becke–Johnson (TB-mBJ) approximation. The band structure shows that all MNBr monolayers are semiconductors with indirect band gaps. The band gap, calculated by TB-mBJ, is larger than that of GGA for both considered compounds. The charge-carrier effective mass increases when going from ZrNBr to HfNBr because of the extra peak of the density of states profile of monolayer HfNBr in the valence band around −0.5 eV, suggesting that ZrNBr should have higher electrical conductivity and HfNBr should have higher Seebeck coefficient. Meanwhile, the monolayered structure of MNBr has intrinsic low lattice thermal conductivity. The results demonstrate that monolayer MNBr has interesting TE properties with n-type doping. Highlights: The band structure shows that MNBr monolayer is semiconductor with indirectband gaps. The phonon spectrums of monolayersMNBr have no negative frequencies. The monolayered MNBr materials facilitates to introduce intrinsic low thermal conductivity. Highest ZT of 0.72/0.84 (0.77/0.83) for p/n-type monolayer ZrNBr/HfNBr are achieved.